If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x-3)+3(4-x)=5
We simplify the equation to the form, which is simple to understand
2(x-3)+3(4-x)=5
Reorder the terms in parentheses
+(+2x-6)+3*(4-x)=5
Remove unnecessary parentheses
+2x-6+3+*(+4-x+)=+5
Reorder the terms in parentheses
+2x-6+(+12-3x)=5
Remove unnecessary parentheses
+2x-6+12-3x=+5
We move all terms containing x to the left and all other terms to the right.
+2x-3x=+5+6-12
We simplify left and right side of the equation.
-1x=-1
We divide both sides of the equation by -1 to get x.
x=1
| 13x-30=21x-14 | | 10+n/6=7 | | -10+x/5=8 | | 2.4+x/2=8 | | .7z+1.9+0.1=5.5-0.4z | | -4m+27=63 | | -2+13q=50 | | 108=12p-32 | | 8-1/3x=12 | | 25n+50=-1500 | | -3/4x=7 | | Y=x^4-2x^3 | | 3w+15=65 | | 25-4/10d=0 | | -30-(-83)= | | 34=13x+(-18) | | -3/4m+9.5=4.75 | | 4x+18=66 | | -3/4m+9.5=0 | | y^2-11y+14=0 | | 1/4a-3=4 | | x^3+2x^2-18x+24=0 | | 2(2r+1)+4=5(r+1) | | -60h+747=747 | | -60h+747=300 | | -15-10=10 | | 6x+4+2x^2-12x=180 | | 6x+4+2x^2-12x=0 | | -60h+747=0 | | 2/3x-9=27 | | -2(x+7)=-8 | | x^1-3x=0 |